Stock market and exchange rate: the great balancing act : a bibliometric analysis / Bee-Hoong Tay - Tay, Bee-Hoong (Universiti Teknologi MARA, Kedah, 2024)
The study presents a bibliometric analysis of the stock market-exchange rate nexus from 1986 to 2023. Data was retrieved from the Scopus database as of August 2023 and analyzed using VOSviewer and Bibliomagika. A total of 477 documents, with a total of 1125 contributing authors, have been obtained. The analysis reveals a persistent interest in this field of research, but with minor variations over time. The results showed that most publications on the stock market and exchange rate were published in 2021 and 2020. The International Review of Economics and Finance is the most significant source title, and most articles were published in journals categorized as economics, econometrics, and finance. The study identifies five clusters of keywords, including asymmetric effect, commodity prices, causal relationship, volatility spillovers, and COVID-19. The findings suggest that future research should focus on exploring the role of exchange rates as a hedge or safe haven during times of uncertainty. The study highlights the lack of a policy perspective in previous studies, emphasizing the significance of exchange rate policy in maintaining stock market stability.